Neisseria meningitidis infection: who, when and where?. Issue 10 (3rd October 2015) - Gianchecchi, Elena; Torelli, Alessandro; Piccini, Giulia; Piccirella, Simona; Montomoli, Emanuele
Abstract : Neisseria meningitidis is a Gram-negative β-proteobacterium responsible for an endemic worldwide infection. The epidemiology and serogroup distribution can change very quickly. The incidence of meningitis infection varies from very rare to more than 1000 cases per 100, 000 of the population yearly. The carriage of N. meningitidis, which represents an exclusive human commensal, is asymptomatic, but in rare cases bacteria proliferate in the CNS and rapidly lead to the death of the affected subjects. Host genetic factors, such as single nucleotide polymorphisms, can promote meningococcal disease, being able to influence the individual predisposition to the pathology. Although a reduction in meningococcal disease has been observed in Europe, a continuous surveillance is necessary to control any possible outbreaks of new hypervirulent clones into populations that could modify the epidemiology of meningococcal infections and the clinical spectrum of affected subjects.